Income and equity effects of crop productivity growth under alternative foreign trade regimes: a CGE analysis for the Philippines - Bautista, Romeo M.; Robinson, Sherman (International Food Policy Research Institute, 1996)
Does a restrictive foreign trade regime reduce the effectiveness of agricultural productivity growth in promoting overall income growth and equity? Based on counterfactual simulations using a multi-sector, computable general equilibrium (CGE) model of the Philippine economy, this paper investigates quantitatively the economywide income and equity effects of crop productivity growh during the green revolution period 1965-80 under alternative trade policies. The results indicate an inequitable distribution of household income gains under the historical, highly restrictive, trade regime. Trade liberalization is found to favor rural over urban households; small-farm households are the biggest gainers among the five household groups, while Metro Manila households are the biggest losers. Such positive redistributive impact is larger the greater is the extent of trade liberalization. The effect on gross domestic product is also significantly positive, so that the movement towards an open trade regime does not involve a tradeoff between the twin objectives of growth and equity.